Calcium balance in hemodialysis: More uncertainty than certainty. Issue 2 (8th January 2020) - Kirmizis, Dimitrios; Basile, Carlo
Abstract: There is controversy about the choice of dialysate calcium concentration (DCa), with strong arguments both in favor of and against the use of a low or high DCa, as they can both be potentially harmful. Evidence suggests that calcium mass balance is positive with a DCa 3.5 mEq/L, negative or neutral with the use of DCa 2.5 mEq/L, whereas both positive and negative balances have been observed with the use of DCa 3.0 mEq/L. Overall, the use of DCa >2.5 mEq/L is usually associated with an increase in serum calcium level and a decrease in serum PTH level and use of lower vitamin D analogue dose, with the opposite effects usually observed with the use of lower DCa. Most of the available evidence is from small‐sized and crossover studies; hence, evidence should be regarded with caution and applied in a patient‐specific manner. As there are a lot of significant unanswered questions regarding calcium balance and the optimal DCa in hemodialysis patients, further high‐quality research is needed to clarify many still unclear aspects of calcium homeostasis and balance in these patients. In conclusion, with the existing evidence the choice of DCa needs to be individualized and contextualized in the setting of each patient's calcium balance needs and homeostatic response, taking also into account oral calcium intake (dietary and medicinal), any other relevant therapy administered, such as vitamin D analogues, the type of renal mineral bone disorder, and associated cardiovascular comorbidity.